COUNTERSPACES AND THE NARRATIVE IDENTITY WORK OF OFFENDER‐LABELED AFRICAN AMERICAN YOUTH. Issue 8 (November 2014) - Case, Andrew D.; Hunter, Carla D.
<x xml:space="preserve">Abstract</x> Through narrative identity work, offender‐labeled African American youth craft positive self‐concepts in the face of denigrating societal messages about their personhood. While past research suggests narrative identity work is largely intrapersonal, recent theory posits that it may also arise through individuals' participation in counterspaces. This 9‐month ethnography explored how a group of offender‐labeled African American youth engaged in narrative identity work through participation in an intervention program that functioned as a counterspace. Findings from observations and interviews suggest youth engaged in narrative identity work by interfacing with the program's unique belief system, and roles, resources, and relationships within the program. These findings highlight specific interpersonal/setting mechanisms that facilitate the narrative identity work of offender‐labeled African American youth, while suggesting important implications for intervening with this population.